2009
DOI: 10.1002/qua.22035
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and dissociation of carbon trioxide on Ag(100)

Abstract: ABSTRACT:Using density functional theory methods, we have studied carbon trioxide, its adsorption and dissociation on Ag(100). In the gas phase, two isomers are found, D 3h and C 2v , with the latter of 2.0 kcal mol −1 lower in energy at the PW91PW91/6-31G(d) level. For CO 3 on Ag(100), the calculated adsorption energy is 91.2 and 89.1 kcal mol −1 for the bi-coord perpendicular and tri-coord parallel structures, respectively. Upon the adsorption, 0.50 ∼ 0.56 electron is transferred from silver to CO 3 , indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…One remaining depression at the border of the image suggests that this novel species consists of three oxygen atoms and one carbon atom, i.e. carbon trioxide, which might be anionic according to ref . In contrast to the O-CO 2 compound discussed above, this species is stable under manipulation as high as 7 eV.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…One remaining depression at the border of the image suggests that this novel species consists of three oxygen atoms and one carbon atom, i.e. carbon trioxide, which might be anionic according to ref . In contrast to the O-CO 2 compound discussed above, this species is stable under manipulation as high as 7 eV.…”
Section: Resultsmentioning
confidence: 86%
“…On Ag(100) it has been suggested that CO 2 can only be stabelized on oxygen precovered surfaces , and the species produced has been attributed to carbonate . Recent DFT (density functional theory) calculations found two almost isonergetic forms of CO 3 , a bicoordinated perpendicular adsorption and a near parallel tricoordinated form . This study calculated a charge transfer of approximately 0.5 e. Furthermore the dissociation of the species into adsorbed oxygen and desorbed CO 2 was calculated.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…For the reaction of CO oxidation on silver, the formation of surface carbonate species (CO 2(g) + O (ad) → CO 3(ad) ) has been identified . Two adsorption structures are bicoordinated perpendicular and tricoordinated parallel with calculated adsorption energy of 91.2 and 89.1 kcal/mol, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All calculations were performed using the suite program of Gaussian 09 . The pw91pw91 hybrid exchange–correlation functional , was used, which has shown good reliability and accuracy in previous reports. For silver, the effective core potential (ECP) of Lanl2 combined with the DZ basis set was adopted, while for O and C atoms, the full electron basis set of 6-31G­(d) was employed. All stationary points on the potential energy surface (PES) were verified by calculated vibrational frequencies at the same theoretical level as used in the geometry optimization. To locate a transition state (TS), a relaxed PES scan was carried out first to find the structure with the highest energy on the reaction path.…”
Section: Computational Details and Modelsmentioning
confidence: 99%